Analysis of the Implementation of Thematic Learning in PAI Subjects at SD IT Abdurrahman Bin 'Auf - Novayani, Irma (STAI Darul Kamal Darul Kamal NW Kembang Kerang, 2026)
This study analyzes the implementation of thematic learning in Islamic Religious Education (PAI) at Abdurrahman Bin 'Auf Islamic Elementary School. The purpose of this study was to analyze the implementation of thematic learning in Islamic Religious Education (PAI) at Abdurrahman Bin 'Auf Islamic Elementary School, which includes lesson planning, lesson implementation, and lesson evaluation. The results of this study indicate that during the planning stage, teachers prepare Lesson Implementation Plans (RPP) that refer to the applicable curriculum. The lesson implementation stage consists of preliminary activities, core activities, and closing activities. The evaluation stage utilizes three main aspects: cognitive, measured through written tests, oral tests, and thematic assignments tailored to PAI material, such as faith, morals, jurisprudence, as well as the Qur'an and Hadith. Affective is measured through religious and social attitudes, including discipline, responsibility, cooperation, honesty, and social awareness. Psychomotor skills are measured through worship practices, work performance, ablution practices, prayer, reading the Qur'an, and memorizing short surahs. Keywords: Implementation, Thematic, Islamic Religious Education